ЗАРУБІЖНИЙ ДОСВІД УПРАВЛІННЯ ФІНАНСОВОЮ СИСТЕМОЮ ТА МОЖЛИВОСТІ ЙОГО ВИКОРИСТАННЯ В УКРАЇНІ (НА ПРИКЛАДІ СПОЛУЧЕНИХ ШТАТІВ АМЕРИКИ) - Кобзєва, Тетяна Анатоліївна (SUPREMANCE OF LAW, 2016)
The article, based on scientific views of scientists studied the experience of the United States of Americas financial system. Proved that pure state mechanism of financial sphere in the US can hardly be introduced in Ukraine, but it does not preclude the possibility of strengthening the control role of the President of Ukraine, the legality, effi ciency and appropriateness of budget funds and increase the autonomy of regional authorities to address in local level of a fi nancial nature.